Pengaruh Utang Luar Negeri, Net Ekspor, dan Belanja Wisatawan Mancanegara Terhadap Cadangan Devisa di Negara Indonesia Tahun 1994-2013 - Togatorop, Sahat Marulitua; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 6, Juni 2017 (pp. 920 - 1156), 2017)
International trade can affect the growth of the economy of the country through eksport and import.One result of international trade is the presence of foreign reserves.The relationship between a country with another countries in general ecccured in debt. The realitionship between countries not just because the of the good, but in the from of visit tourism. This study aims to determine how the effects of foreign debt, net exports, and foreign tourists shopping on reserves in Indonesia. The data used in this research is secondary data with the period 1994-2013. Data analysis technique used is multiple linear regression with SPSS 16.00 equipped with the classical assumption and standardized coefficient beta. Based on test results, simultaneously found that the three independent variables have an influence on the foreign exchange reserves in Indonesia, while partial external debt net exports and foreign tourists spending significant positive effect on the country's foreign exchange reserves in Indonesia. In addition, foreign debt is the independent variable that has a dominant influence on the results of the analysis standardized coefficient beta.
Keywords: cadangan devisa; belanja wisatwan mancanegara; net ekspor; utang luar negeri